Common writing : essays on literary culture and public debate - Collini, Stefan, 1947- (Oxford University Press, 2016)
In a series of penetrating and readable essays, Stefan Collini explores aspects of the literary and intellectual culture of Britain from the early twentieth century to the present. He focuses chiefly on writers, critics, historians, and journalists who occupied wider public roles as cultural commentators or intellectuals, as well as on the periodicals and other genres through which they attempted to reach such audiences. Among the figures discussed are T.S. Eliot, Graham Greene, J.B. Priestley, C.S. Lewis, Kingsley Amis, Nikolaus Pevsner, and Hugh Trevor-Roper.